2008
DOI: 10.1158/1078-0432.ccr-08-0255
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Therapy by Inhibition of p21waf1 in Human Malignant Mesothelioma

Abstract: Purpose: The p21 cyclin-dependent kinase inhibitor was frequently expressed in human malignant pleural mesothelioma (MPM) tissues as well as cell lines. Recent data indicate that p21keeps tumor cells alive after DNA damage, favoring a survival advantage. In this study, we assessed the possibility of p21suppression as a therapeutic target for MPM. Experimental Design: We established two different MPM-derived (from H28 and H2052 cells) subclones using vector-based short hairpin RNA (shRNA). Then, chemosensitivit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 25 publications
3
29
1
Order By: Relevance
“…Our functional studies identified that DPD inhibits cancer cell migration and tumor growth through p21 activation by a p53-independent pathway. These results were consistent with other reports and support the notion that p21 has a crucial role in anticancer therapy (29,30).…”
Section: Discussionsupporting
confidence: 94%
“…Our functional studies identified that DPD inhibits cancer cell migration and tumor growth through p21 activation by a p53-independent pathway. These results were consistent with other reports and support the notion that p21 has a crucial role in anticancer therapy (29,30).…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the accumulation of p21 may be involved in, but is not absolutely required for, the induction of apoptosis. However, p21, a cyclin-dependent kinase inhibitor, can induce growth arrest by inhibiting cyclin-dependent kinases that drive cell cycle progression, sensitizing cancer cells to chemotherapy (36). The Bcl-2 family is comprised of structurally related proteins that can either inhibit (i.e., Bcl-2) or promote (i.e., Bax) cell death (37).…”
Section: Discussionmentioning
confidence: 99%
“…20,24,25 In addition, the induction of p21 WAF1 that occurs after exposure to various cytotoxic stimuli can inhibit the apoptosis process in malignant hematopoietic cells [26][27][28] and solid tumor cells. 5,29 In the clinical setting, elevated p21 WAF1 expression has been associated with chemotherapy resistance and poor prognosis in acute myeloid leukemia, 30,31 while an association with p21 WAF1 induction and poor clinical outcome in ALL has been proposed. 32 Mechanisms proposed to explain the anti-apoptotic role of p21 WAF1 include transcriptional regulation of anti-apoptotic genes, 33 inhibition of CDKs that are involved in activation of caspases integral to apoptosis downstream of mitochondrial disruption, 9 or direct inhibition of pro-apoptotic proteins, such as procaspase-3, caspase-8 or apoptosis signal-regulating kinase 1.…”
Section: Introductionmentioning
confidence: 99%